2009
DOI: 10.1007/s10764-009-9378-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping Sites of Rhinopithecus brelichi at Yangaoping, Guizhou

Abstract: Arboreal primates spend about half of their lives at sleeping sites; hence, selection of sleeping sites is crucial for individual survival, and data concerning them is important for conservation efforts. We collected data on sleeping sites for a group of the endangered snub-nosed monkey (Rhinopithecus brelichi) at Yangaoping (27°58′N, 108°45′E) from January 2006 to December 2007. All sleeping sites were located in the mid-slope and in the shadow of ridges facing the northeast and southeast. The monkeys remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 28 publications
0
32
2
1
Order By: Relevance
“…Accordingly, their night roosts were significantly lower in elevation than their feeding sites and day roosts. Contrary to Xiang et al [2010], our results do not support the finding that the monkeys sleep near their feeding site, although critical comparisons are difficult because the authors observed the monkeys from 13 fixed locations, and the spatial scale they used to describe the monkeys' various activity areas (including sleeping sites) was more coarsegrained than ours. Also, it is unclear how feeding site was defined in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, their night roosts were significantly lower in elevation than their feeding sites and day roosts. Contrary to Xiang et al [2010], our results do not support the finding that the monkeys sleep near their feeding site, although critical comparisons are difficult because the authors observed the monkeys from 13 fixed locations, and the spatial scale they used to describe the monkeys' various activity areas (including sleeping sites) was more coarsegrained than ours. Also, it is unclear how feeding site was defined in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…Heymann 1995 for Saguinus mystax and Saguinus fuscicollis; Radespiel et al 1999 Zhang et al 2011 for Rhinopithecus roxellanae), minimise the distance to the first feeding tree of the following morning (von Hippel 1998) and have a low probability of branch loss under windy conditions (Di Bitetti et al 2000). For primates living in temperate climes, avoiding climatic stress can also be an important consideration in sleepingsite choice (Anderson 2000;Li et al 2010;Xiang et al 2010;Zhang et al 2011). For species in limestone areas, access to water may also be key (Wang et al 2011 for T. francoisi).…”
Section: Introductionmentioning
confidence: 99%
“…In open vegetation, specific sleeping tree traits such as height, (e.g., tall tree), diameter at breast height, (e.g., large), and surrounding coverage, (e.g., dense), are all associated with the quality of a sleeping site (Cui et al 2006;Di Bitetti et al 2000;Fan and Jiang 2008). For example, snubnosed monkeys (Rhinopithecus brelichi) use tall trees with large crowns and high percentages of canopy cover, which provide shelter from snow, rain, and predation (Xiang et al 2010). Sleeping in trees with dense foliage also offers better protection than sleeping on bare deciduous trees (Xiang et al 2010).…”
mentioning
confidence: 99%
“…For example, snubnosed monkeys (Rhinopithecus brelichi) use tall trees with large crowns and high percentages of canopy cover, which provide shelter from snow, rain, and predation (Xiang et al 2010). Sleeping in trees with dense foliage also offers better protection than sleeping on bare deciduous trees (Xiang et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation